Видовой состав и численность синантропных грызунов в Молдове - Михайленко, А.Г.; Унтура, А.А. (Вестник зоологии, 1993)
Data are presented concerning the relative number and species composition of small mammals in buildings (mainly on food and agricultural objects) in Moldova as to materials of registrations for 1983-1990. 39103 day traps have been worked out, 2678 animals of six species being caught. Out of them Norway rat (57.2 % of all the caught animals) and house mouse (42.0%) are constant synantrops (eusynantrops), while common field mouse (0.52%), common vole (0.15%), scilly shrew (0.04%) and lesser shrew (0,04 %) are semi-synantrops (hemisynantrops). Black rat as a species does not inhabit Moldova, only melanists of grey rat are found in catches. The average number of synantrops has been observed for many years: 5.9 % of the catching rate in traps at meat and milk enterprises, 5.4 % — at bakery enterprises, 3.3 % — at fruit and vegetable storehouses, 7.1 %—at groceries and public catering enterprises, 8.9 % — at cattle breeding farms, 5.6 — at other objects.